2012
DOI: 10.1063/1.4733691
|View full text |Cite
|
Sign up to set email alerts
|

Influences of annealing temperature on structural characterization and magnetic properties of Mn-doped BaTiO3 ceramics

Abstract: Polycrystalline samples of BaTiO3 doped with 2.0 at. % Mn were prepared by solid-state reaction at various temperatures (Tan) ranging from 500 to 1350 °C, used high-pure powders of BaCO3, TiO2, and MnCO3 as precursors. Experimental results obtained from x-ray diffraction patterns and Raman scattering spectra reveal that tetragonal Mn-doped BaTiO3 starts constituting as Tan ≈ 500 °C. The Tan increase leads to the development of this phase. Interestingly, there is the tetragonal-hexagonal transformation in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 48 publications
5
25
0
Order By: Relevance
“…The red shifting of the peak may be due to the larger atomic mass of Mn than Ti [35]. Another consequence of Mn doping is the formation of three new vibrational bands observed at 539 cm -1 , 603 cm -1 and 676 cm -1 of which the later two is reported earlier for the Mn doped BTO [11,35]. …”
Section: Effect Of Dopants In Bto Using Raman Spectramentioning
confidence: 82%
See 1 more Smart Citation
“…The red shifting of the peak may be due to the larger atomic mass of Mn than Ti [35]. Another consequence of Mn doping is the formation of three new vibrational bands observed at 539 cm -1 , 603 cm -1 and 676 cm -1 of which the later two is reported earlier for the Mn doped BTO [11,35]. …”
Section: Effect Of Dopants In Bto Using Raman Spectramentioning
confidence: 82%
“…The Fe doping in A-site of BaTiO 3 ceramics hassled to a relaxor ferroelectric behaviour reported by Maikhuri et al [9]. A rich profusion of reports is available in the case of Mn doping in B-site with reasonably good values of magnetisation [10,11]. The effect of concurrent doping with combination of Ca (A-site)-Fe (B-site) and Zn (A-site)-Mn (B-site) in BaTiO 3 is investigated by Chakraborty and Ray [12] and Das et al [13] respectively.…”
mentioning
confidence: 91%
“…From the above result we demonstrated that all these three oxidation states of Mn are present in our BaTi 1-x Mn x O 3 samples. Usually Mn 2+ with greatest r ion is found in BaTi 1-x Mn x O 3 which is annealed in the reducing atmosphere conditions[4,25]. The electron configuration d 4 of Mn 3+…”
mentioning
confidence: 99%
“…BaTiO 3 (BTO) is known to have a perovskite structure where 3d transition metal can easily substitute for titanium atom due to their similarity in size and valence [5]. BaTiO 3 has excellent ferroelectric and dielectric properties such as high dielectric constant and low dielectric loss, chemical stability and low toxicity [6][7]. Basically, multiferroic materials can be fabricated by means of two routes.…”
Section: Introductionmentioning
confidence: 99%
“…Basically, multiferroic materials can be fabricated by means of two routes. One route is the composite combining a ferroelectric material with a ferromagnetic material while the other is doping of magnetic impurities into a ferroelectric host material [1][2][3][5][6][7]. In this work, we present a systematic study on BaTiO 3 substituted with different concentration of Co at the Ti site.…”
Section: Introductionmentioning
confidence: 99%